Design economic evolution in the jewellery industry through design process - Hashim, Hema Zulaika; Abd Rahman, Khairul Aidil Azlin; Alli, Hassan; Raja Ahmad Effendi, Raja Ahmad Azmeer (Faculty of Science and Technology, University of El Oued, 2018)
Design is the designer’s thumbprint of aesthetic values imprinted in a creative role to exhibit capability in realizing a customer’s innermost desires for the perfect jewellery. Design plays an important role in the jewellery industry as it determines the success of a jeweller in terms of integrity and brand name within a certain class or categorization in the jewellery business. The design process prior to achieving satisfying jewellery will depend on a designer's understanding of need, science, technical knowledge, creativity, time frame and costing. These factors translate into economics, business performance, profitability, market dominance, expansion and sustainability of a jeweller. Findings from indepth observation and consideration to this study have exposed an understanding to factors significant in the evolving production of jewellery designs that should influence Malaysia’s jewellery industry.